Management analysis of the Indonesian National Lawn Bowls Team at the 2018 Asian Para Games - Chandra Febriyan Fitriawan; Muchsin Doewes; Sapta Kunta Purnama (Nicolaus Copernicus University in Toruń, 2020)
Abstract The purpose of this study was to investigate the management of Lawn Bowls Indonesia's national team. This research is a qualitative and descriptive study. Data collection techniques using observation, interviews, and document analysis. The data validity technique uses two triangulation techniques, namely data triangulation and method triangulation. Data analysis was carried out in four stages namely: data collection stage, data reduction stage, data presentation stage, conclusion drawing stage. The results showed that the management role of Lawn Bowls was already good. This has been proven in the application of the four main functions in management including Planning, Organizing, Directing, Controlling. The condition of the infrastructure owned by Lanw Bowls Indonesia is good even though the field does not meet the standards. Lawn Bowls Indonesia coaches have done a good job as a trainer. Lawn Bowls Indonesia coaches also prioritize discipline towards athletes or players. Aside from being a motivator for athletes to always be diligent in practicing, maintaining body condition and stamina as well as the drive to continue to excel. The source of coaching funds is still supported by the Ministry of Youth and Sports through the Indonesian National Paralympic Committee (NPC). The nutrition law for Indonesian bowls has been fulfilled. This is because the athlete's diet has been prepared and controlled directly by Lawn Bowls Indonesia's management. Meeting energy needs through carbohydrate consumption, through protein consumption and through fat consumption. Lawn Bowls Indonesia's Achievements In the event, the Lawn Bowls sports branch won 15 medals consisting of 5 gold, 4 silver, 6 bronze. It has been proven that Lawn Bowls Indonesia is ranked 2nd in the 2018 Asian Paragames event in Jakarta. Keywords: Management, Indonesian National Lawn Bowls, Asian Para Games